Emergence of Vancomycin-Resistant Enterococci - Louis B. Rice (Emerging Infectious Diseases, 2001)
Vancomycin and ampicillin resistance in clinical Enterococcus faecium strains has developed in the past decade. Failure to adhere to strict infection control to prevent the spread of these pathogens has been well established. New data implicate the use of specific classes of antimicrobial agents in the spread of vancomycin-resistant enterococci (VRE). Extended-spectrum cephalosporins and drugs with potent activity against anaerobic bacteria may promote infection and colonization with VRE and may exert different effects on the initial establishment and persistence of high-density colonization. Control of VRE will require better understanding of the mechanisms by which different classes of drugs promote gastrointestinal colonization.